Fabrication of MgAlSiCrFe Low-Density High-Entropy Alloy by Mechanical Alloying and Spark Plasma Sintering - Singh N.; Shadangi Y.; Goud G.S.; Pandey V.K.; Shivam V.; Mukhopadhyay N.K. (My University, 2025)
An equiatomic Mg20Al20Si20Cr20Fe20 (at.%) low-density high-entropy alloy (LDHEA) was synthesized by mechanical alloying (MA) and consolidated by spark plasma sintering (SPS) techniques. The phase identification, chemical composition, fine microstructural features and thermal stability of the mechanical alloyed powder and the spark plasma sintered (SPSed) compacts were discerned through X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and differential scanning calorimetry (DSC) techniques. The LDHEA powder after mechanical alloying for 60 h exhibited a nanocrystalline BCC phase (a = 0.2887 ± 0.005 nm) as a major one along with the minor fraction (~ 3%) of undissolved Si. The 60-h milled powder was consolidated through SPS at 800 ℃ (1073 K). The SPSed sample exhibited the presence of a major B2-type AlFe phase (cP2; a = 0.2889 nm) along with a parent disordered BCC phase and a minor amount of Al13Fe4 (mC102; a = 1.549 nm, b = 0.808 nm, c = 1.248 nm), β-Al3Mg2 (cF1168; a = 2.824 nm) and Cr5Si3 (tI32; a = 0.917 nm, c = 0.463 nm) phases. Attempts were made to explore the mechanical properties of the LDHEA through microindentation techniques. The hardness and yield strength were evaluated to be ~ 7 GPa and ~ 2100 MPa respectively. The density of the sintered sample was found to be around 4.38 g cm−3, which is around 99.98% of the theoretical density. The phases evolved during MA and SPS were explained with the help of the thermodynamic parameters and property diagrams generated through the CALPHAD approach using Thermo-Calc software. © 2021, The Indian Institute of Metals - IIM.